Emerging roles of protein kinase CK2 in abscisic acid signaling - Vilela, Belmiro; Pagès, Montserrat; Riera, Marta (Frontiers in Plant Science, 2015)
The phytohormone abscisic acid (ABA) regulates many aspects of plant growth and development as well as responses to multiple stresses. Post-translational modifications such as phosphorylation or ubiquitination have pivotal roles in the regulation of ABA signaling. In addition to the positive regulator sucrose non-fermenting-1 related protein kinase 2 (SnRK2), the relevance of the role of other protein kinases, such as CK2, has been recently highlighted. We have recently established that CK2 phosphorylates the maize ortholog of open stomata 1 OST1, ZmOST1, suggesting a role of CK2 phosphorylation in the control of ZmOST1 protein degradation (Vilela et al., 2015). CK2 is a pleiotropic enzyme involved in multiple developmental and stress-responsive pathways. This review summarizes recent advances that taken together suggest a prominent role of protein kinase CK2 in ABA signaling and related processes.